2022
DOI: 10.3389/fnut.2022.944200
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet as a Modifiable Risk Factor for Thyroid Nodular Disease and Thyroid Cancer: Results From a Pilot Study

Abstract: Iodine deficiency is the most important established nutritional risk factor for the development of thyroid nodular disease. Nevertheless, to the best of our knowledge, to date no study focused on the association between the adherence to the Mediterranean diet (MD) and thyroid nodular disease. Adherence to the MD was evaluated using the PREvención con DIetaMEDiterránea (PREDIMED) questionnaire. Physical activity, smoking habits, and anthropometric parameters were studied. PREDIMED was used to evaluate the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 80 publications
(96 reference statements)
0
17
0
Order By: Relevance
“…Adherence to MD was assessed using the 14-item Prevención con Dieta Mediterránea (PREDIMED) questionnaire, which has been validated before [ 17 ]. As previously reported [ 18 , 19 ], a trained nutritionist administered the questionnaire to all studied subjects during an in-person interview. Each item was assigned a score of 1 or 0, and the PREDIMED score was calculated based on the total scores [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Adherence to MD was assessed using the 14-item Prevención con Dieta Mediterránea (PREDIMED) questionnaire, which has been validated before [ 17 ]. As previously reported [ 18 , 19 ], a trained nutritionist administered the questionnaire to all studied subjects during an in-person interview. Each item was assigned a score of 1 or 0, and the PREDIMED score was calculated based on the total scores [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…There is some evidence to suggest that the anti-inflammatory and antioxidant mechanisms of MD may be helpful in promoting thyroid health and reducing the risk of thyroid nodules and cancer [ 15 , 16 ]. The formation of thyroid nodules is influenced by various factors, including genetics, iodine intake, and inflammation.…”
Section: Endocrine Axes and The Mediterranean Dietmentioning
confidence: 99%
“…Research has shown that MD may have a beneficial effect for various endocrine disorders [ 9 , 11 14 ]. For example, studies have suggested that higher adherence to MD could help to lower the risk of thyroid disorders, including autoimmune thyroiditis [ 15 , 16 ]. Additionally, MD has been associated with improved male and female reproductive health [ 13 , 14 ], including increased sperm quality [ 13 ] and improvement of the clinical picture of PCOS [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to MD was assessed using the 14-item Prevención con Dieta Mediterránea (PREDIMED) questionnaire, which has been validated before [17]. As previously reported, a trained nutritionist administered the questionnaire to all study participants during an in-person interview [18,19]. Each item was assigned either a score of 1 or 0, and the PREDIMED score was calculated based on the total scores.…”
Section: Adherence To Mediterranean Dietmentioning
confidence: 99%